Image Registration in Medical Robotics and Intelligent Systems: Fundamentals and Applications. (14th August 2019) - Liu, Jun; Singh, Gurpreet; Al'Aref, Subhi; Lee, Benjamin; Oleru, Olachi; Min, James K.; Dunham, Simon; Sabuncu, Mert R.; Mosadegh, Bobak
Abstract : Medical image registration, by transforming two or more sets of imaging data into one coordinate system, plays a central role in medical robotics and intelligent systems from diagnostics and surgical planning to real‐time guidance and postprocedural assessment. Recent advances in medical image registration have made a significant impact in orthopedic, neurological, cardiovascular, and oncological applications.The recent literature in medical image registration is reviewed, providing a discussion of their fundamentals and applications. Within each section, the registration techniques are introduced, classifying each method based on their working mechanisms, and discussing their benefits and limitations are discussed. Recently, machine learning has had an important impact on the field of image registration, yielding novel methods and unprecedented speed. The validation of registration methods, however, remains a challenge due to the lack of reliable ground truth. Medical image registration will continue to make significant impacts in the area of advanced medical imaging, as the fusion/combination of multimodal images and advanced visualization technology become more widespread. Abstract : Medical image registration, by transforming two or more sets of imaging data into one coordinate system, plays a central role in medical robotics and intelligent systems from diagnostics and surgical planning to real‐time guidance and postprocedural assessment. Herein, the recent literature in medical image registration is reviewed and a discussion of their fundamentals and applications is provided.